Kesejahteraan Petani dan Aset-Aset Penentunya - Marlina Wirmas (Jurnal Agro Ekonomi, 2021)
The low contribution of agricultural sector’s income shows unequal proportion with the large number of workers that it accommodate. Former policy which prioritize improvement on economic performance such as increasing production, jobs, and decreasing poverty; although generate a fairly good result, it evidently widen the socio-economic gap between the agricultural workforce with others. Thus, the paradigm to measuring well-being using those indicators should be extended by put forward the human aspect as the center of evaluation. Capability approach is used to identify farmer’s well-being that reflected on the freedom to do and to be according to the value whom it believe. Evaluation conducted by identifying level of capability based on its level of availability and functioning of five category of assets which represent the modal and opportunity needed by farmers to realize their desire purpose. This reseach was conducted in Ampek Angkek district, Agam Regency, West Sumatera Province by sending questionnaire to qualified farmers to rate the indicators which consist of 51 types from five group of assets. The analysis find that on average measurement, community capability index is on the fairly good condition which available assets provide benefit and functions to farmers perform its job at farming process. But comparation between the five group of assets shows that farmer have not get maximum range of access to individual tangible asset (represent physical modal & level of wealth) and economic institutional asset (represent easiness access in work). Regarding these result, effort that necessary to be executed is to increase the level of human and social capital from the internal capability of the farmers, and put an integration on agricultural development program with other sectors in order to create wider access for farmers to develop their business.